A novel molecular method for identification of Oenococcus oeni and its specific detection in wine - Marques, Ana P. (2011)
Oenococcus oeni is a species of lactic acid bacteria with economic interest in winemaking. Using both in silico and in vitro analyses, a molecular method was developed that allows the identification of O. oeni isolates and its detection from wine samples. The method is based on the amplification of 16S rRNA gene with universal primers followed by restriction with the endonuclease FseI, generating two fragments of 326 and 1233 bp. Among wine bacteria, the FseI recognition sequence is only found in the 16S rRNA gene of O. oeni, ensuring the specificity of the method. The use of Whatman FTA cards for DNA extraction and purification is an efficient and interesting alternative to current methods, as samples can be easily collected at wineries by a non-specialized technician, stored at room temperature and sent in a mail envelope to the analytical laboratory for processing. The proposed method, with a detection limit between 102 and 103 cfu/mL and a full turnaround time of ca. 8 h, ensures the rapid and reliable detection of O. oeni in wine samples during winemaking surveillance and wine quality control.